Thixotroic behaviour study of clayey soils from the lacustrine deposits of bogotá high plateau (2018)
Thixotropy is a distinctively rheological (time-dependent) phenomenon, which is found in many complex materials, especially colloidal systems as fine-grained soils. Clays are materials that can recover their initial strength after remoulding. The estimation of such recovering allows optimising the designs of geotechnical structures and then reducing the construction costs. This paper presents the results of a study that evaluates the thixotropy phenomenon of clayey soils. The work methodology involved an experimental plan composed of five phases: (i) extraction of samples; (ii) physical and mechanical characterisation of the undisturbed samples; (iii) remoulding of samples after testing; (iv) storage of remoulded samples; and (v) evaluation of undrained shear strength recovering for 0, 15, 30, and 60 days after remoulding. Undisturbed samples were collected using Shelby tube from the municipality of Madrid, near Bogotá, in Colombia. Results were analysed in terms of sensitivity degree because this parameter allows estimating the shear strength recovering. Findings show that clayey soils from lacustrine deposits of Bogota high plateau do not loss completely all of their original mechanical properties after remoulding and exhibit a medium sensitive behaviour. Conclusions indicate there is a recovering of undrained shear strength along the time, in which the samples will recover their original state about one year after remoulding.